Interactions between climate change and infrastructure projects in changing water resources: An ethnobiological perspective from the Daasanach, Kenya - Junqueira, André Braga (J Ethnobiol, 2021)
The fast and widespread environmental changes that have intensified in the last decades are bringing disproportionate impacts to Indigenous Peoples and Local Communities. Changes that affect water resources are particularly relevant for subsistence-based peoples, many of whom already suffer from constraints regarding reliable access to safe water. Particularly in areas where water is scarce, climate change is expected to amplify existing stresses in water availability, which are also exacerbated by multiple socioeconomic drivers. In this paper, we look into the local perceptions of environmental change expressed by the Daasanach people of northern Kenya, where the impacts of climate change overlap with those brought by large infrastructure projects recently established in the Omo River. We show that the Daasanach have rich and detailed understanding of changes in their environment, especially in relation to water resources. Daasanach understand observations of change in different elements of the social-ecological system as an outcome of complex interactions between climatic and non-climatic drivers of change. Our findings highlight the perceived synergistic effects of climate change and infrastructure projects in water resources, driving multiple and cascading impacts on biophysical elements and local livelihoods. Our results also demonstrate the potential of Local Ecological Knowledge in enhancing the understanding of complex social-ecological issues, such as the impacts of environmental change in local communities. To minimize and mitigate the social-ecological impacts of development projects, it is essential to consider potential synergies between climatic and socioeconomic factors and to ensure inclusive governance rooted in local understandings of environmental change.